Altered climate leads to positive density‐dependent feedbacks in a tropical wet forest. (8th April 2020) - Bachelot, Benedicte; Alonso‐Rodríguez, Aura M.; Aldrich‐Wolfe, Laura; Cavaleri, Molly A.; Reed, Sasha C.; Wood, Tana E.
Abstract: Climate change is predicted to result in warmer and drier Neotropical forests relative to current conditions. Negative density‐dependent feedbacks, mediated by natural enemies, are key to maintaining the high diversity of tree species found in the tropics, yet we have little understanding of how projected changes in climate are likely to affect these critical controls. Over 3 years, we evaluated the effects of a natural drought and in situ experimental warming on density‐dependent feedbacks on seedling demography in a wet tropical forest in Puerto Rico. In the +4°C warming treatment, we found that seedling survival increased with increasing density of the same species (conspecific). These positive density‐dependent feedbacks were not associated with a decrease in aboveground natural enemy pressure. If positive density‐dependent feedbacks are not transient, the diversity of tropical wet forests, which may rely on negative density dependence to drive diversity, could decline in a future warmer, drier world. Abstract : Climate change is predicted to result in warmer and drier Neotropical forests relative to current conditions, yet little is known about how these forests will respond. Using the first warming experiment in a tropical rainforest and a natural drought event, we found dramatic changes in seedling demographics which could threaten the diversity of these forests. These changes could result from complex effects of climate on plant natural enemies and mutualists.